DEVELOPMENT OF CHARACTER EDUCATION BASED ON LOCAL WISDOM IN INDEGENOUS PEOPLE TENGAHAN SEDANGAGUNG - Dina Anika Marhayani (STKIP Singkawang, 2016)
The character education is built from the values of local wisdom that diverse. The value of local wisdom contains noble values of the ancestor of nation that can be used as capital to establish a nation with good and strong character. The role of local wisdom can be used to develop a character education. This study have reviewed same jurnal literature and article about development of character education based on local wisdom. The first part in the study will introduce the meaning of charater, character education, and local wisdom. The second part will discuss relation of character education and local wisdom, social culture on indigenous peoples Tengahan Sendangagung, the values of the local wisdom on indigenous peoples Tengahan Sendangagung, and the wisdom of the local indigenous people to develop a character education. Finally, the last part of this paper will explain some values of the local wisdom to develop character education.